Kinect-Driven Humanoid Robot for Mimetic Interaction (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This paper presents an innovative approach to human-robot interaction through the use of a Kinect-type device for capturing the movement of a human operator, which is then accurately reproduced by a humanoid robot. The robot, standing at 110 cm, mimics a reduced-sized human and is crafted utilizing advanced 3D printing technology. The core of this system lies in its ability to capture human limb movements via the Kinect device, analyse the angular movements, and process this data to control the robot to replicate these movements identically. This methodology not only enhances the fidelity of movement replication but also broadens the scope of applications for such technology. Potential applications include but are not limited to rehabilitation, where the robot can assist or guide physical therapy exercises, entertainment, through performances or interactive displays, and educational settings, where it can serve as a tool for learning about robotics and human anatomy. This research marks a significant step forward in the development of humanoid robots that can seamlessly integrate into various aspects of human life, offering both functional and educational benefits.